BTS’S MAGICAL SPELL IN THE AGE OF ARTIFICIAL INTELLIGENCE: THE POISONED CHALICE OF FREEDOM THAT I SWALLOWED KNOWINGLY - Kim, Kwangsik (WILAYAH: The International Journal of East Asian Studies, 2024)
The question this paper aims to address is whether we can find a philosophical message for the age of artificial intelligence in the songs of BTS. The research objective of this paper is to show that we can find a philosophical message for the age of artificial intelligence in the songs of BTS. The research method of this paper is to first find a philosophical message for the era of artificial intelligence through Yuval Harari's book Homo Deus, then analyze the lyrics of BTS's song "Blood Sweat and Tears" based on the message, find a philosophical message for the era of artificial intelligence contained in the song, and support the philosophical message with Nietzsche's Philosophy of the Superhuman. The research finding of this paper is that we can find a philosophical message for the era of artificial intelligence through the song "Blood, Sweat & Tears" by BTS, which can also be supported by Nietzsche's Philosophy of the Superhuman. The message is: "Swallow the poisoned chalice of freedom, even though you know it's poisoned!". The conclusion that can be drawn from this finding is that the humanity that needs to be renewed in the age of AI is Homo sapiens, who thinks for himself. It is not AI-recommended Hommo Sapiens, not AI represented Homo Sapiens, but Self-deciding free Homo Sapiens, a free human who wanders, crosses over, thinks and decides for oneself.